O‘ZBEK ADABIYOTIDA PSIXOLOGIZM MUAMMOSINING O‘RGANILISHI - Ro‘ziyeva Yulduz Qahramon qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
In this article, the opinions of our literary scholars are given regarding the question of the role of psychologism in the analysis of the literary work, in particular, the research related to the image of the hero‟s psyche.